Veterinary and sanitary assessment of the quality and safety of food raw materials and products in the Zhytomyr region, 2024 - Kotelevych, V.; Pinsky, О.; Huralska, S.; Hоncharenko, V.; Budnik, T. (Scientific Progress & Innovations, 2025)
The aim of this study was to provide a veterinary and sanitary assessment of the quality and safety of food raw materials and products in the Zhytomyr region in 2024. According to the analysis of reporting documentation, in 2024, specialists from the state veterinary and sanitary examination laboratories (SVSEL) of the Zhytomyr Regional State Laboratory of the State Service of Ukraine on Food Safety and Consumer Protection (ZRSL SSUFSCP) examined and conducted 410,976 laboratory tests of food raw materials and food products. A total of 45.365 tons of products were not approved for sale, and 6,031 unsatisfactory test results were obtained, including 20 carcasses, 1,592 cases of invasive and non-contagious diseases, of which 1,011 were echinococcosis. Due to invasive and non-contagious diseases, 3.234 tons of products were disposed of. The results of studies on the presence of toxic elements, pesticides, antibiotics, radionuclides revealed only an excess of permissible levels for the content of 137Cs in the Korosten district: in 10 samples of fresh mushrooms and berries (113.6 Bq/kg; 638 Bq/kg; 590.4 Bq/kg; 584 Bq/kg; 934 Bq/kg; 1100 Bq/kg; 573 Bq/kg; 950 Bq/kg; 900 Bq/kg; 1550 Bq/kg; compared with the DR-2006 norm of 500 Bq/kg); in 2 samples of medicinal plants and 1 sample of vegetables (43.5 Bq/kg). Specialists in the veterinary examination department of the Zhytomyr Regional State Laboratory for Food Safety and Consumer Protection are conducting extensive work on controlling antibiotic residues in food raw materials and products. In particular: in 2024, 1,004 samples were examined and 1,588 laboratory tests were conducted. 460 samples were examined by the microbiological method and 1,044 laboratory tests were conducted; no positive results were found. 182 tests were conducted by the enzyme-linked immunosorbent assay method: 138 tests for chloramphenicol content; 44 tests for melamine content. 362 samples of raw milk were tested with the Rapid-Test 4 in 1 screening test systems (antibiotics of the β-lactam, tetracycline, streptomycin, and chloramphenicol groups). In order to control the epizootic situation, specialists of the Zhytomyr Regional State Laboratory of the State Service for Food Safety and Consumer Protection have developed and are implementing long-term measures for the prevention of especially dangerous animal diseases. According to the scope of accreditation for veterinary and sanitary well-being and food safety, specialists implement state policy, including in the critical infrastructure sector in the Zhytomyr region.